Rhizobium inoculation and exogenous melatonin synergistically increased thermotolerance by improving antioxidant defense, photosynthetic efficiency, and nitro-oxidative homeostasis in Medicago truncatula - Irshad, Annie; Rehman, Rana Naveed Ur; Dubey, Shikha; Khan, Muhammad Azam; Yang, Peizhi; Hu, Tianming (Frontiers in Ecology and Evolution, 2022)
Global warming negatively affects plant growth due to the detrimental effects of high temperature-induced heat stress. Rhizobium inoculation (RI) and exogenous melatonin (MT) have shown a positive role in resisting abiotic stress. However, their synergistic effect on avoiding heat-induced damages in Medicago truncatula has not been studied yet. Hence, the objective of the present study was to evaluate the impact of these amendments (RI and MT) to ameliorate the heat damages in Medicago truncatula. The study was comprised of two factors: (1) heat-induced stress: (i) optimum temperature (26±1 °C): (23±1 °C) (day: night), (ii) moderate heat (35±1 °C): (28±1 °C), and (iii) severe heat (41±1 °C): (35±1 °C) for 72 h, and (2) amendments: (i) no RI + no MT (NRI+NMT), (ii) Rhizobium inoculation (RI), (iii) 60 μM melatonin (MT), and (iii) RI+MT. Results showed that the combined application of RI and MT was better than their individual applications, as it prevented heat-induced membrane damages by declining the hydrogen peroxide (34.22% and 29.78%), superoxide anion radical (29.49% and 26.71%), malondialdehyde contents (26.43% and 21.96%), and lipoxygenase activity (44.75% and 25.51%) at both heat stress levels as compared to NRI+NMT. Moreover, RI+MT treated plants showed higher antioxidative and methylglyoxal detoxification enzymes (Gly I and Gly II) activities under heat stress. While, NRI+NMT treated plants showed a higher level of methylglyoxal contents (47.99% and 46.71%) under both levels of heat stress. Relative to NRI+NMT plants, RI+MT pretreated plants exhibited improved heat tolerance as indicated by higher chlorophyll (37.42% and 43.52%), carotenoid contents (32.41% and 47.08%), and photosynthetic rate (42.62% and 64.63%), under moderate and severe heat stress, respectively. Furthermore, RI+MT pretreated plants had considerably higher indole-3 acetic acid and abscisic acid concentrations under moderate (54.02% and 53.92%) and severe (68.36% and 64.61%) heat stress conditions. Similarly, plant dry biomass, NPK uptake, nitric oxide, and nitrate reductase activity were high in RI+MT treated plants, under both levels of stress. Therefore, this study advocates the positive synergistic effect of RI and MT pretreatment against moderate and severe heat-induced stress and for possible maintenance of plant growth under changing scenarios of global warming.